Substance P Hinders Bile Acid-Induced Hepatocellular Injury by Modulating Oxidative Stress and Inflammation - Dahyeon Lee; Jeong Seop Park; Doyoung Kim; Hyun Sook Hong (MDPI AG, 2022)
Liver failure is an outcome of chronic liver disease caused by steatohepatitis and cholestatic injury. This study examined substance P (SP) effect on liver injury due to cholestatic stress caused by excessive bile acid (BA) accumulation. Chenodeoxycholic acid (CDCA) was added to HepG2 cells to induce hepatic injury, and cellular alterations were observed within 8 h. After confirming BA-mediated cellular injury, SP was added, and its restorative effect was evaluated through cell viability, reactive oxygen species (ROS)/inflammatory cytokines/endothelial cell media expression, and adjacent liver sinusoidal endothelial cell (LSEC) function. CDCA treatment provoked ROS production, followed by IL-8 and ICAM-1 expression in hepatocytes within 8 h, which accelerated 24 h post-treatment. Caspase-3 signaling was activated, reducing cell viability and promoting alanine aminotransferase release. Interestingly, hepatocyte alteration by CDCA stress could affect LSEC activity by decreasing cell viability and disturbing tube-forming ability. In contrast, SP treatment reduced ROS production and blocked IL-8/ICAM-1 in CDCA-injured hepatocytes. SP treatment ameliorated the effect of CDCA on LSECs, preserving cell viability and function. Collectively, SP could protect hepatocytes and LSECs from BA-induced cellular stress, possibly by modulating oxidative stress and inflammation. These results suggest that SP can be used to treat BA-induced liver injury.